Intersection of Art and Religion in African Cultures - Victor Onibere; Peter O. O. Ottuh (Peradaban Journal of Religion and Society, 2024)
This study investigates the complex interplay between art and religion within African cultures. By examining various art forms, including sculptures, masks, paintings, and textiles, this study explores how these artistic expressions have been used to convey religious beliefs and spiritual experiences. Through a multidisciplinary lens encompassing art history, anthropology, and religious studies, the research analyzes the symbolic language embedded in these artworks, to reveal the narratives and spiritual messages they communicate. It also explores the roles of artists, artisans, and religious practitioners as mediators between cultures who create and employ art within religious rituals.The study examines the transmission of artistic techniques and sacred knowledge across generations, revealing the artistic processes and the spiritual intentions behind religious artworks. Furthermore, it investigates how art functions as a bridge between the physical and spiritual realms, facilitating communication with deities, ancestors, and spirits. By examining the historical, social, and cultural forces that have shaped the evolution of art and religion in Africa, including the impacts of colonialism and globalization, this research explores how African artists and religious practitioners have been adapted and transformed traditional art forms while preserving their core spiritual essence. Through in-depth case studies from diverse African regions and cultural groups, this research enhances our understanding of the complex relationship between art and religion, highlighting their significance in shaping African spiritual worldviews and cultural heritage.